Prevalence of coronary artery disease and the associated risk factors among the patients attending the medicine department in a tertiary care teaching hospital in the North Eastern Zone in India - Akhtar, Naushad; Paul, Pritama; Kumar, Tapas; Paul, Uttam K. (International Journal of Advances in Medicine, 2023)
<div id="chakra-toast-manager-bottom-right" style="position: fixed; z-index: var(--toast-z-index, 5500); pointer-events: none; display: flex; flex-direction: column; bottom: env(safe-area-inset-bottom, 0px); right: env(safe-area-inset-right, 0px);" role="region" aria-live="polite"> Background: Coronary artery disease (CAD) is characterized by the narrowing or obstruction of coronary arteries, leading to inadequate blood supply to the heart. In India, CAD has become a major public health issue, particularly in the North Eastern Zone. This study aims to illuminate CAD, its causes, and its unique prevalence patterns within India, with a specific focus on the North Eastern Zone. Methods: A cross-sectional study was conducted over a year at a tertiary care teaching hospital in India's North Eastern Zone. A sample of 154 patients with coronary artery disease was selected through structured questionnaires, clinical examinations, vital signs assessments, and 12-lead ECGs. Data analysis was done with proper equipment. Results: The study revealed an overall CAD prevalence of 4.24% among 2468 patients attending the Medicine OPD. Males had a higher prevalence across age groups, except for the 20-30-year-olds, where no females participated. Urban areas exhibited a significantly higher CAD prevalence (68.83%) compared to rural areas (31.17%). Statistically significant gender differences were observed in several risk factors, with males more likely to exhibit hypertension, hyperlipidemia, diabetes mellitus, obesity, smoking, and ischemic heart disease. Urban residents also showed a higher prevalence of various CAD risk factors compared to rural residents, except for alcohol consumption, which was more common in rural areas. Conclusions: The findings corroborate existing literature, highlighting gender disparities and urban-rural differences in CAD prevalence and risk factors. This study contributes valuable insights into CAD epidemiology in India, particularly in the North Eastern Zone.